By Using ETABS Planning, Designing and Analysis of a Commercial Building Consisting of Flat Slabs Considering Earthquake Induced Forces (International Journal of Innovative Research in Computer Science & Technology, 2022)
Structures consisting of Flat slabs posses’  great advantage over conventional structures with usual  slab beam design. Because of the freedom to design space,  shorter construction time, architectural functional as well  as economical elements, flat slab building structures have  significant benefits. Flat slab structural systems are  substantially more flexible than standard RC frame  systems due to the lack of deep beams and shear walls,  making them more vulnerable during seismic occurrences.  The slab column connections, i.e., the shear force in the  slab at the connection, should always keep its bearing  capacity even at maximum displacements, is altogether a  vital moment in the design of these systems. Building  construction has a significant impact on the behaviour of  flat slab buildings during earthquakes. As a result of this  fact, it is necessary to take due consideration and to  discover how to assure the safety of tall structures against  earthquake forces.
Keywords: Aspect Ratio; Flat slab structures; Punching shear; Ratio of Slenderness(H/B); Response Spectrum